Metagenomic analysis fecal microbiota of dysentery-like diarrhoea in a pig farm using next-generation sequencing - Chen, Xi; Guo, Qing; Li, Ying-Ying; Song, Tie-Ying; Ge, Jun-Qing (Frontiers in Veterinary Science, 2023)
Porcine enteric diseases including swine dysentery involves a wide range of possible aetiologies and seriously damages the intestine of pigs of all ages. Metagenomic next-generation sequencing is commonly used in research for detecting and analyzing pathogens. In this study, the feces of pigs from a commercial swine farm with dysentery-like diarrhea was collected and used for microbiota analysis by next-generation sequencing. While Brachyspira spp. was not detected in diarrheal pig fecal samples, indicating that the disease was not swine dysentery. The quantity of microbial population was extremely lowered, and the bacterial composition was altered with a reduction in the relative abundance of the probiotics organisms, Firmicutes and Bacteroidetes, with an increase in pathogens like Fusobacterium and Proteobacteria, in which the specific bacteria were identified at species-level. Viral pathogens, porcine circovirus type 2, porcine lymphotropic herpesviruses 1, and porcine mastadenovirus A were also detected at pretty low levels. Carbohydrate-active enzymes (CAZy) analysis indicated that the constitute of Firmicutes and Bacteroidete were also changed. Further, the Kyoto Encyclopedia of Genes and Genomes (KEGG) alignment analysis indicated that the microbiota of diarrheal pigs had a lower ability in utilizing energy sources but were enriched in multi-drug resistance pathways. Comprehensive Antibiotic Resistance Database (CARD) and Virulence Factors of Pathogenic Bacteria (VFDB) analysis indicated that genes for elfamycin and sulfonamide resistance and the iron uptake system were enriched in diarrheal pigs. This revealed potential bacterial infection and can guide antibiotic selection for treating dysentery. Overall, our data suggested that alterations in both the population and functional attributes of microbiota in dysentery pigs with decreased probiotic and increased pathogenic microorganisms. These results will help elucidate the mechanism of dysentery-like diarrhea and the development of approaches to control the disease.